Aflibercept a new target therapy in cancer treatment: a review. Issue 3 (December 2015) - Ricci, Vincenzo; Ronzoni, Monica; Fabozzi, Teresa
Abstract: Angiogenesis is the process through which new blood vessels are formed from pre-existing vessels and is essential for the growth of all solid tumors. Vascular endothelial growth factor (VEGF) is a regulator of angiogenesis, which is crucial for tumor growth and metastasis. Its inhibition with antiangiogenic drugs is thought to improve delivery of chemotherapy through vascular normalization and disruption of tumor vasculature. Aflibercept is a recombinant fusion protein of the VEGF receptor (VEGFR)1 and VEGFR2 extracellular domains that binds to VEGF-A, VEGF-B, placental growth factor (PlGF) 1 and 2. Aflibercept has demonstrated preclinical efficacy in different tumor types and exerts its antiangiogenic effects through regression of tumor vasculature, remolding of vasculature, and inhibition of new tumor vessel growth. This review examines the effects of aflibercept on tumor vasculature and on different types of solid tumors, and explores the preclinical and clinical benefits of inclusion aflibercept into anticancer treatment strategies.